Participatory Evaluation of Common Bean for Drought and Disease Resilience Traits in Uganda - Mukankusi, Clare Mugisha; Nkalubo, Stanley T.; Katungi E; Luyima G; Awio, Bruno; Radeny, Maren A.O.; Kinyangi, James (2015)
The use of genetic resources to respond to occurring and unpredictable climatic changes is one of the coping mechanisms for small scale farmers in Africa. This paper summarizes findings of a participatory action research (PAR) project evaluating different common bean (Phaseolus vulgaris) varieties with nine farmer groups across nine villages in two CCAFS sites of Rakai and Hoima districts in Uganda. Six and fifteen bean varieties including local landraces, farmer variety (commonly grown by farmers), Uganda officially released varieties and new germplasm bearing different characteristics were evaluated with over 300 farmers in replicated trials in the first season of 2012, and two seasons of 2013, respectively. The study provides evidence that breeders and farmers look out for similar traits, with yield being the major driver, and in most cases end up with the same results with a few discrepancies. Some key lessons emerged from the findings. First, making blanket variety and management recommendations to cover large physical areas is erroneous. Site and context specific recommendations, especially in the view of the variability in climatic conditions and soils are probably the best option. Second, the results highlight the need for plasticity in bean varieties (i.e. ability to change structure and function when exposed to changes in the environments hence suitability to a wide range of environments) in addition to having farmer preferred traits. Lastly, the project also highlighted the ability, capacity and willingness of farmers to adopt and adapt new technologies in the face of varying climate scenarios.